<span>Simplifying
49x^2 + -9 = 0
Reorder the terms:
-9 + 49x^2 = 0
Solving
-9 + 49x^2 = 0
Solving for variable 'x'.
Move all terms containing x to the left, all other terms to the right.
Add '9' to each side of the equation.
-9 + 9 + 49x^2 = 0 + 9
Combine like terms: -9 + 9 = 0
0 + 49x^2 = 0 + 9
49x^2 = 0 + 9
Combine like terms: 0 + 9 = 9
49x^2 = 9
Divide each side by '49'.
x^2 = 0.1836734694
Simplifying
x^2 = 0.1836734694
Take the square root of each side:
x = {-0.428571429, 0.428571429}
hope this helps!!</span>
8(4n + 13) = 6n
Use distributive property so :8 (4n) = 32n and 8(13) = 104
32n + 104 = 6n
Subtract 32n from each side and you will get:
104 = 26n
then you divide each side by 26 and your answer will be:
n = 4
C=(-10;5). If you want an explanation I would be happy to explain it
Step-by-step explanation:
9x - 2x = 8 + 5
7x = 13
x =13÷7
x = 1.8571
approximately = 1.86
I think this is it